The nursing of skin metastasis on the puncture site of peripherally inserted central catheter in a patient with lung cancer. Issue 4 (July 2019) - Xie, Ling L; Pu, Dan; Xiang, Fen Q; Li, Ying J
Objective: To report a case of lung cancer metastasizing to skin from peripherally inserted central catheter puncture and to analyze the causes and treatment of this event. Methods: In August 2016, one patient with lung cancer developed a nodule on the puncture site of peripherally inserted central catheter. The nodule was 1 cm × 1 cm in size and soft in texture, whose color was similar to that of the skin; the surface was smooth and integral without tenderness, bleeding, or exudates. After removing the catheter, the nodule ruptured and was liable to bleeding on touching and grew up gradually ever since. Cytological examination of the nodule revealed tumor cells infiltration, after which nodule resection was performed. Result: The patient's wound healed up well, and no other masses were found on the skin surface around the whole body. The pathological examination of the surgical specimen suggested metastatic pulmonary adenocarcinoma. Conclusion: The case of lung cancer metastasizing to skin from peripherally inserted central catheter puncture is rare and may be attributed to the aggressiveness of tumor, the age of the patient, and the duration and location of peripherally inserted central catheter. Active treatment of distant metastasis could improve the life quality and prolong the survival of the patients.